Analisis Kinerja Operasional Bongkar Muat Barang Di Kade Baru Timur Pelabuhan Sunda Kelapa - S, Susmitha Theresia (Institut Transportasi dan Logistik Trisakti, 2024)
The role of ocean transport is essential to economic, social, government, defense and security for island areas like Indonesia. Indonesia is rich in islands that own more vast oceans than land. With Indonesia's harbor one of the key functions in assisting with the mobility of products and consumer goods from around the world. Sunda coconut harbor was established in 1527 and was operating from the 5th century onward, having an area of 1,760 acres [760 ha] and a pool of 16,470 acres [16,470 ha], the main harbor having an area of 12,700 feet [3,250 m] long and an area of 1,200 feet [1,200 m]. With the decision made by the sea crossing UM.002/3818/DJPL-11 on the harbor's standard operating service as one way to increase sea transport infrastructure, there should be an evaluation of the quality of operating performance of one of the harbor's oil plants. The harbor's operational performance of operations can be done by analysis by the drill method (berth hesancy ratio), BTP (berth the troughtput), BT (Berthing Time), YOR (yard sixancy ratio), ytp (yard throughput), TSH (ton of ship hour), sor (shed camp any ratio). Analysis explains that the 2000 ships' 2022 visit with the flow of ships, berthing time in 2022 73.52 hours. The performance of using the pier in march-december was (81.17%) in 2022 was too high to be compared with government standards. D productivity.